EMPIRICAL ANALYSIS OF FEMALE PARTICIPATION IN EDUCATION, PARLIAMENTS, AND WORKFORCE ON ECONOMIC DEVELOPMENT IN MUSLIM COUNTRIES - Nurul Hasanah; Ira Eka Pratiwi (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2020)
The main objective of this study is to investigate female participation on education, parliament, and workforce in Muslim countries. By using secondary data over the period from 2010 until 2014 and parametric analysis, it can be concluded that there is a significant difference between female participation in Middle East and non-Middle East countries. The estimation showed that the average of female in parliament and female labor force participation are higher in non-Middle East countries. Furthermore, the study also estimates the influence of female participation on economic growth. By using multiple regression panel data method, processed by E-Views, the result found that both female literacy rate and female participation in parliament have a positive and significant relationship with economic growth in Muslim countries. Meanwhile, the result of female labor force participation and female unemployment rate show insignificant effect on economic growth.